MAKNA VERBA MAJEMUK BAHASA JEPANG KAESU - Lina Rosliana; Ida Lailatussoimah (Diponegoro University, 2018)
(Title: Semantic Meaning of Japanese Compound Verbs kaesu). Compound verbs (fukugoudoushi) are compound words formed from a combination of at least two morphemes that have new grammatical meanings and functions as a verb. Compound verbs in Japanese can be formed from the combination of nouns with verbs (N + V), verbs with verbs (V1 + V2), adjectives with verbs (A + V), and adverbs with verbs (AD + V). The results of the combination structure above can produce diverse meanings. One of the causes is the presence of several verbs forming the back of the elements whose characteristics have many meanings. For example in the verb kaesu. Besides acting as an element forming the back, kaesu can also act as an element forming the front. Kaesu can form many compound verbs with different meanings. The aim of this research is to describe the semantic meaning of compound verbs –kaesu. The data being used are obtained from the website and some online news articles. The data were collected by library study, observation and writing technique. Then, the research data were analyzed using distributional method. The results of the analysis are presented by an informal method which is explained with simple words.